2005
DOI: 10.1001/archinte.165.19.2278
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of the Autoimmune Health Effects of a Cargo Aircraft Disaster

Abstract: Occupational exposure to the aircraft disaster resulted in an excess of long-term self-reported autoimmune-like symptoms in exposed professional assistance workers, but there was no difference between exposed and nonexposed workers in the prevalence of autoantibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Firstly, direct unknown biological effects of disaster-related exposures to hazardous materials could have contributed to the lower HRQoL of exposed workers. However, this seems less plausible because no consistent significant differences were found previously between these exposed and non-exposed workers regarding various clinical parameters tested in urine and blood samples [29,30]. Furthermore, no excess morbidity due to disaster-related exposures was predicted in retrospective risk evaluations [3,4].…”
Section: Discussionmentioning
confidence: 92%
“…Firstly, direct unknown biological effects of disaster-related exposures to hazardous materials could have contributed to the lower HRQoL of exposed workers. However, this seems less plausible because no consistent significant differences were found previously between these exposed and non-exposed workers regarding various clinical parameters tested in urine and blood samples [29,30]. Furthermore, no excess morbidity due to disaster-related exposures was predicted in retrospective risk evaluations [3,4].…”
Section: Discussionmentioning
confidence: 92%
“…The study design was approved by the Medical Ethics Committees of the two medical facilities involved in this project: the VU University Medical Center and the Onze Lieve Vrouwe Gasthuis in Amsterdam. Previous reports of the Epidemiological Study Air Disaster in Amsterdam have already shown that exposed rescue workers reported more physical and psychological health complaints than nonexposed colleagues (Huizink et al, 2003;Slottje et al, 2005a). No consistent significant differences between exposed and nonexposed workers were found with regard to several clinical parameters in urine and blood samples, such as blood cell counts, creatinine clearance, and autoantibody serology.…”
Section: Overviewmentioning
confidence: 81%
“…In contrast to anti-cardiolipin antibodies, lupus anticoagulant is rarely present in asymptomatic individuals (18 ); thus, our findings cannot be applied to other markers of antiphospholipid syndromes, such as lupus anticoagulant.…”
Section: Discussionmentioning
confidence: 67%
“…Anti-cardiolipin antibodies can be detected in up to 7% of the healthy population (10,11,18 ) and might be present in increased concentrations in selected patient groups, such as those suffering from chronic viral infections, including HIV or hepatitis. In addition, Delgado Alves et al (19 ) reported that anti-cardiolipin antibodies frequently interact with other plasma lipids, including HDL-cholesterol and apolipoprotein A1.…”
Section: Discussionmentioning
confidence: 99%